Insomnia in Chinese College Students With Internet Addiction: Prevalence and Associated Clinical Correlates - Shen, Yanmei; Jin, Xingyue; Zhang, Yaru; Huang, Chunxiang; Lu, Jianping; Luo, Xuerong; Zhang, Xiang Yang (Frontiers in Psychiatry, 2020)
Background: Internet addiction (IA) has gained more and more attention for its negative impact on the subjects’ study and daily life. However, in a large sample, there is little research on the association between IA and insomnia in Chinese college students. This study aimed to investigate the prevalence of insomnia and its related risk factors among Chinese college students with IA. Methods: A cross-sectional design was used to investigate 627 Chinese college students with IA. Each student completed a survey on demographic data, Internet addiction (Revised Chinese Internet Addiction Scale), depression (Self-Rating Depression Scale), insomnia (Athens Insomnia Scale), anxiety (Self-Rating Anxiety Scale), and suicidal behavior. Binary logistic regression analysis was employed to adjust for confounding factors. Results: The prevalence of insomnia among students with IA was 54.86%. Compared with IA students without insomnia, IA students with insomnia were more likely to be younger, smoking, drinking, have anxiety, depression, suicidal ideations, suicide plans and suicide attempts (all p<0.05). Moreover, drinking [OR,1.664; 95% confidence interval (CI),1.139-2.431; p=0.008], anxiety (OR,2.321; 95%CI,1.116-4.826; p=0.024) and suicidal ideation (OR,1.942; 95% CI:1.295-2.911; p=0.001) were independently associated with insomnia in IA students. Conclusions: Insomnia is very common in Chinese IA students. drinking, anxiety and suicidal ideation are independently correlated with insomnia. This study provides valuable evidence for school counselors and clinical professionals to assess Internet addiction, insomnia and suicide risk.